Markov Chain Analysis: Peramalan Pangsa Pasar dan Pola Perpindahan Merek berdasarkan Persepsi Konsumen pada Produk Minyak Goreng di Surabaya - Triwijayati, Anna; Astanto, Merlin (Jurnal Widya Manajemen & Akuntansi, 2005)
Cooking oil is one of the most needed food supplies. Many cooking oil brands are available in the market to provide demand consumption to this product. However, now days, arises of petroleum prices influence reduction cooking oil consumption.